Geochemical characteristics of back-arc basin lower crust and upper mantle at final spreading stage of Shikoku Basin: an example of Mado Megamullion - Norikatsu Akizawa (SpringerOpen, 2021)
Abstract This paper explores the evolutional process of back-arc basin (BAB) magma system at final spreading stage of extinct BAB, Shikoku Basin (Philippine Sea) and assesses its tectonic evolution using a newly discovered oceanic core complex, the Mado Megamullion. Bulk and in-situ chemical compositions together with in-situ Pb isotope composition of dolerite, oxide gabbro, gabbro, olivine gabbro, dunite, and peridotite are presented. Compositional ranges and trends of the igneous and peridotitic rocks from the Mado Megamullion are similar to those from the slow- to ultraslow-spreading mid-ocean ridges (MOR). Since the timing of the Mado Megamullion exhumation corresponds to the very end of the Shikoku Basin opening, the magma supply was subdued and highly episodic, leading to extreme magma differentiation to form ferrobasaltic, hydrous magmas. In-situ Pb isotope composition of magmatic brown amphibole in the oxide gabbro is identical to that of depleted source mantle for mid-ocean ridge basalt (MORB). In the context of hydrous BAB magma genesis, the magmatic water was derived solely from the MORB source mantle. The distance from the back-arc spreading center to the arc front increased away through maturing of the Shikoku Basin to cause MORB-like magmatism. After the exhumation of Mado Megamullion along detachment faults, dolerite dikes intruded as a post-spreading magmatism. The final magmatism along with post-spreading Kinan Seamount Chain volcanism were introduced around the extinct back-arc spreading center after the opening of Shikoku Basin by residual mantle upwelling.